Dynamic Modeling of Multi-Agent Systems Using MAS-ML Tool - Lima, Francisco R. O. de; Feijó, Állan R.; Rocha Jr, Robert M.; Nogueira, Igor B.; Gonçalves, Enyo J. T.; Freire, Emmanuel S. S.; Cortés, Mariela I. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
Given the diversity of entities comprising multi-agent systems (MAS), the modeling of the dynamic aspects is complex and error prone. Thus, the existence of a tool capable of modeling of these systems and validating them automatically, can be crucial in order to increases the productivity. The goal of this work is present the evolution of MAS-ML tool to provide the support to the dynamic diagrams of sequence and activities defined on the MAS-ML 2.0 language.